ANTIBACTERIAL ACTIVITIES OF CIHERANG RICE (Oryza sativa L. Var. Ciherang) ETHANOL EXTRACT AGAINST Enterotoxigenic Escherichia coli (ETEC) - Dinda Sari; Bening Fitri Rini; Alifia Anisya; Feby Oktavia; Ali Zainal Abidin; Marieska Verawaty (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
Enterotoxigenic Escherichia coli (ETEC) is one of the most common bacteria that cause a large number of diarrhea in infants, children and adults living in developing countries. Potential activity of Ciherang rice’s (Oryza sativa L. var. Ci-herang) leaves’ extract as antibacterial agent against the ETEC was investigated in this research. The secondary metabolite was extracted, its antibacterial activity, and its minimum inhibitory concentration (MIC) against the ETEC were determined. This study indicated the leaf extract of Ciherang rice in the ethanol fraction contained tannins, saponins, flavonoids, alkaloids, and terpenoids. It showed strong antibacterial activity against ETEC (at concentration of 100%); the extract activity test had diameter of inhibition zone around 11.12 mm with MIC value of 11.12 mm. This study suggested the ethanol leaf extract at various concentrations showed significant effect (p<0.05) toward the diameter of the inhibition zone. The Ethanol leaves extract of Ciherang rice at 100% of concentration has a MIC value of 11.37 mm.